2012
DOI: 10.1007/s10566-011-9167-1
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes for Youth with Severe Emotional Disturbance: A Repeated Measures Longitudinal Study of a Wraparound Approach of Service Delivery in Systems of Care

Abstract: Background Systems of care is a family centered, strengths-based service delivery

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 28 publications
0
18
0
Order By: Relevance
“…In previous studies of school-age samples, the RADS-2 had three-week test–retest reliability of .87, strong criterion-related validity, and Cronbach’s alphas of .91 to .93, (Reynolds & Mazza, 1998). The measure has strong validity and reliability in clinical and nonclinical samples of children and adolescents (Reynolds, 2002) and has been used successfully with children as young as 9 years old (Laurent, Joiner, & Catanzaro, 2011; Painter, 2012). In our sample, the measure showed excellent internal consistency (Cronbach’s alpha = .91 at wave 1 and .93 at wave 2).…”
Section: Methodsmentioning
confidence: 99%
“…In previous studies of school-age samples, the RADS-2 had three-week test–retest reliability of .87, strong criterion-related validity, and Cronbach’s alphas of .91 to .93, (Reynolds & Mazza, 1998). The measure has strong validity and reliability in clinical and nonclinical samples of children and adolescents (Reynolds, 2002) and has been used successfully with children as young as 9 years old (Laurent, Joiner, & Catanzaro, 2011; Painter, 2012). In our sample, the measure showed excellent internal consistency (Cronbach’s alpha = .91 at wave 1 and .93 at wave 2).…”
Section: Methodsmentioning
confidence: 99%
“…The wraparound model is widely used on children programs and has previously been shown to be effective with children (e.g., Suter & Bruns, 2009;Cox et al, 2010;Painter, 2012), adult torture survivors (e.g., McColl et al, 2010, Raghavan, Rasmussen, Rosenfeld, & Keller, 2013McFarlane & Kaplan, 2012, Kira, 2002 and homeless veterans (Smelson et al, 2013). The systemic model has been shown to be effective in Somali refugee children (Ellis et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has used surveys and questionnaires to assess the presence of individual protective factors for children and families (McCammon, 2012). Painter (2012) assessed individual protective factors (e.g., self-confidence in one's abilities; ability to manage emotions) using the Behavioral and Emotional Rating Scale (BERS-2; Epstein, 2004) every six months throughout a two-year period of time in wraparound services. Findings revealed that parent-rated protective factors significantly increased after just six months in wraparound; however, youths' self-rated protective factors did not change over time (Painter, 2012).…”
Section: Individual Protective Factorsmentioning
confidence: 99%
“…Painter (2012) assessed individual protective factors (e.g., self-confidence in one's abilities; ability to manage emotions) using the Behavioral and Emotional Rating Scale (BERS-2; Epstein, 2004) every six months throughout a two-year period of time in wraparound services. Findings revealed that parent-rated protective factors significantly increased after just six months in wraparound; however, youths' self-rated protective factors did not change over time (Painter, 2012). Protective factor data based on information from multiple sources (e.g., reports from wraparound facilitators based on information gathered from all team members) may help to further our understanding of wraparound outcomes.…”
Section: Individual Protective Factorsmentioning
confidence: 99%